Comparative and phylogenetic analysis of complete chloroplast genomes from seven Neocinnamomum taxa (Lauraceae) - Cao, Zhengying; Yang, Linyi; Xin, Yaxuan; Xu, Wenbin; Li, Qishao; Zhang, Haorong; Tu, Yuxiang; Song, Yu; Xin, Peiyao (Frontiers in Plant Science, 2023)
The genus Neocinnamomum (Lauraceae) contains valuable oilseed and medicinal tree species. In order to explore the genetic structure and evolutionary characteristics of the Neocinnamomum chloroplast genome and to resolve the species relationships within the genus, comparative genomic and phylogenetic analyses were performed on the whole chloroplast genome sequences of 51 samples representing seven Neocinnamomum species. The whole Neocinnamomum chloroplast genome size ranged from 150,753-150,956 bp, with a GC content of 38.8%-38.9%. A total of 128 genes were annotated within the Neocinnamomum chloroplast genome, including 84 protein coding genes, 8 rRNA genes, and 36 tRNA genes. Between 71-82 SSRs were detected, among which A/T base repeats were the most common. The chloroplast genome contained a total of 31 preferred codons. Three highly variable regions, trnN-GUU-ndhF, petA-psbJ, and ccsA-ndhD, were identified with Pi values > 0.004. Based on the whole chloroplast genome phylogenetic tree, the phylogenetic relationships among the seven Neocinnamomum species were determined. N. delavayi and N. fargesii were the most closely related species, and N. lecomtei was identified as the most basal taxon. In this study, the characteristics and sequence variation of the chloroplast genomes of seven Neocinnamomum species were revealed, and the genetic relationship among the species was clarified. The results of this study will provide a reference for subsequent molecular marker development and phylogenetic research of Neocinnamomum.